Novel methodology based on biomimetic superhydrophobic substrates to immobilize cells and proteins in hydrogel spheres for applications in bone regeneration - Lima, A. C. (2013)
Cell-based therapies for regenerative medicine have been characterized by the low retention and integration of injected cells into host structures. Cell immobilization in hydrogels for target cell delivery has been developed to circumvent this issue. In this work mesenchymal stem cells isolated from Wistar rats bone marrow (rMSCs) were immobilized in alginate beads fabricated using an innovative approach involving the gellification of the liquid precursor droplets onto biomimetic superhydrophobic surfaces without the need of any precipitation bath. The process occurred in mild conditions preventing the loss of cell viability. Furthermore, fibronectin (FN) was also immobilized inside alginate beads with high efficiency in order to mimic the composition of the extracellular matrix. This process occurred in a very fast way (around 5 min), at room temperature, without aggressive mechanical strengths or particle aggregation. The methodology employed allowed the production of alginate beads exhibiting a homogenous rMSCs and FN distribution. Encapsulated rMSCs remained viable and were released from the alginate for more than 20 days. In vivo assays were also performed, by implanting these particles in a calvarial bone defect to evaluate their potential for bone tissue regeneration. Microcomputed tomography and histological analysis results showed that this hybrid system accelerated bone regeneration process. The methodology employed had a dual role by preventing cell and FN loss and avoiding any contamination of the beads or exchange of molecules with the surrounding environment. In principle, the method used for cell encapsulation could be extended to other systems aimed to be used in tissue regeneration strategies.